Amplification in gyro-travelling-wave tubes—dispersion relation and gain-bandwidth characteristics - Rao S.J.; Jain P.K.; Basu B.N. (My University, 2025)
The interaction in a cylindrical waveguide, loaded with a thin hollow beam of electrons gyrating in helical paths to give a gyro-TWT configuration, is investigated. The beam perturbation is estimated by solving the relativistic Vlasov's equation and a dispersion relation describing the beam-wave interaction is obtained for an electron beam of zero guiding centre spread. The dispersion relation is interpreted following the Pierce type approach to a conventional TWT to obtain a gain equation of the well known form G = A+BCN. The influence of the basic parameters such as beam voltage, beam current, velocity pitch factor and DC magnetic flux density on the gain-frequency response is extensively investigated to find a trade-off between the gain and bandwidth. The results show that an increase in beam current improves the gain whereas at higher beam voltages one gets a flat gain-frequency response though at the cost of the gain. A high value of the velocity pitch factor gives a higher gain however at frequencies close to the waveguide cut-off thereby making the device prone to oscillations. It is found that the gyro-TWT interaction is extremely sensitive to the variation in DC magnetic flux density. © 1996 Taylor & Francis Group, LLC.